Business Opportunity : Takoyaki Express / Aida Maisarah Zakaria - Zakaria, Aida Maisarah (2021)
Since 2019, our country has been facing pandemic corona virus (Covid19), the Prime Minister has announced that our country needs to stay at home because of Movement Control Order (MCO) to prevent the spread of the virus. All people in this country will start a new norm which is wear a face mask, social distancing, and stay at home. Based on the experience, people need a food to stay alive. So, I come out with one idea to improve a Takoyaki Express for people get need a snack that provides some healthy and beauty for them.